Progress of basic competencies, literacy and enrolment of children in Matlab: re-visiting baseline villages - Rana, AKM Masud; Ahmed, Syed Masud (BRAC Research and Evaluation Division (RED), 2019)
The Assessment of Basic Competency (ABC) test was administered under BRAC ICDDR, B Joint Research Project to explore the progress of enrolment, basic competency and literacy of children during the seven years period (1992-1999) under study in rural Matlab, Bangladesh. The test was administered initially in 1992 followed by 1995 and 1999. A total of 749 children was included in 1992 test and followed by 1703 in 1995 and 969 in 1999. All three types of households viz BRAC member, eligible non-member and non-eligible households were included in the samples who were aged 11-15 years irrespective of their enrolment status. The study villages were selected from the 60 villages of baseline survey, where socioeconomic survey was carried out simultaneously. Findings revealed that enrolment has increased from 77% in 1992 to 89% in 1995 and to 93% in 1999. Enrolment of girls was found to be higher than boys in the follow up tests. Both enrolment and drop-out rate was higher among the eligible non-member household's children. The rate of basic competence increased from 17.4% in 1992 to 26.4% in 1995 but dropped to 18.1% in 1999. One notable feature was that the children from BRAC schools did somewhat better compared to children in similar schools elsewhere, being more pronounced in 1995. The gender gap has slightly narrowed down in terms of learning achievement from 1992 to in 1995 though girls were still lagging behind. However in 1999, girls performed better than boys did in learning achievement.